Strategic Security Partnership between the AU and the EU: The Case of Sudan - Abdurrahim Sıradağ (Akademik İncelemeler Dergisi)
Peace and security are seen as the main prerequisites for economic and political development and for the developing world in particular. The international community seeks to sustain peace, security and stability but the achievement of this objective is subject to many constraints. These include political and economic factors, security problems and outside influences. The European Union (EU) and the African Union (AU) have strengthened their relations in the areas of conflict prevention and crisis management, and endeavored to preserve peace and stability on the continent over the last decade. This article will highlight how the EU and the AU are cooperating for the establishment of peace in Sudan.